Effects of Coconut Flower Sugar and Oligofructose Osmotic Process on Mass Exchange and Sensory of Pineapple Rings - ยืนยงพุทธกาล วิชมณี; อิทธิโสภณกุล ธีรารัตน์; แสนกล้า ศุภิสรา; คุ้มทรัพย์ สุทธิดา (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
Healthy sweeteners are beneficial for healthy food production. Coconut flower sugar is low in a glycemic index value. Oligofructose is prebiotic which lower in sweetness intensity than sucrose. This research aimed to study the effect of coconut flower sugar and oligofructose mixtures on mass exchange and sensory perception in osmosis process of pineapple rings. The ratio of coconut flower sugar to oligofructose was varied to 60:0, 45:15, 30:30, 15:45 and 0:60 (g/ 100 g), and compared with a sucrose solution. After osmosis of pineapple rings for 360 min., it was found that the sugar solutions showed different effects on mass exchange value, moisture content and sensory acceptance score (p < 0.05), but not on aw (p ≥ 0.05). The solution of 60 g/ 100 g coconut flower sugar resulted in the highest WL and WR, but the lowest overall sensory acceptance score (p < 0.05). The best condition was a ratio of coconut flower sugar to oligofructose as 15:45 g/100 g. After osmosis for 360 min., the WL, SG and WR values were equal to 17.69, 6.82 and 10.70 %, respectively. The overall sensory acceptance score was 7.03. An application of osmotic solution in a mixed form is an appropriate approach to osmotic dehydration of fruit.